2010
DOI: 10.1093/annhyg/meq025
|View full text |Cite
|
Sign up to set email alerts
|

The Diesel Exhaust in Miners Study: IV. Estimating Historical Exposures to Diesel Exhaust in Underground Non-metal Mining Facilities

Abstract: We developed quantitative estimates of historical exposures to respirable elemental carbon (REC) for an epidemiologic study of mortality, including lung cancer, among diesel-exposed miners at eight non-metal mining facilities [the Diesel Exhaust in Miners Study (DEMS)]. Because there were no historical measurements of diesel exhaust (DE), historical REC (a component of DE) levels were estimated based on REC data from monitoring surveys conducted in 1998–2001 as part of the DEMS investigation. These values were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 23 publications
0
48
1
Order By: Relevance
“…The effects of diesel engine emissions on the mine air quality, fine particle concentrations, and occupational exposures have also been widely investigated (Scheepers et al 2003;Noll et al 2007;Vermeulen et al 2010). In a previous study conducted in an underground gold mine, it was shown that diesel exhaust can contribute by a fraction of 78%-98% to the PM 2.5 mass and by >90% to the PM 2.5 carbon concentration (McDonald et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of diesel engine emissions on the mine air quality, fine particle concentrations, and occupational exposures have also been widely investigated (Scheepers et al 2003;Noll et al 2007;Vermeulen et al 2010). In a previous study conducted in an underground gold mine, it was shown that diesel exhaust can contribute by a fraction of 78%-98% to the PM 2.5 mass and by >90% to the PM 2.5 carbon concentration (McDonald et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…An additional complication is the uncertainty in measurement of dose. A crucial component of the exposure assessment is the comparison with a gold standard or other independent type of corroboration (1, 2). Corroborating measurements of exposure that include biological measurements are particularly valuable if repeated over time (3) and if the measurements are biologically meaningful (4).…”
Section: Introductionmentioning
confidence: 99%
“…For example we were able to reproduce reasonably well results contained in Figure 1 of Stewart et al (2010), Tables 1, 4 and the table in the Appendix of Coble et al (2010), Table 1 and Figure 2 of Vermeulen et al (2010a), and Tables 1 and 2 and Figure 2 from Vermeulen et al (2010b). We would not expect to get exact matches in many cases due to differences in imputed data.…”
Section: Our Workmentioning
confidence: 53%
“…DPM, diesel particulate matter; RD, respirable dust; ROC, rcspirable organic carbon; SCD, submicron combustible dust; SD, submicron dust; SEC, Submicron elemental carbon; SOC, submicron organic carbon; TD, total dust, TEC, total elemental carbon; TOC, total organic carbon. a Surveys: the MSHA MIDAS (1976–2001); the DEMS (1998–2001) (Coble et al, 2010; Vermeulen et al, 2010b); the MESA/BoM (1976–1977) (Sutton et al, 1979); the feasibility study for the DEMS in Facility B (1994) (Stanevich et al, 1997): compliance visits by the State of New Mexico, MSHA hard copy reports, and the mining facilities (1954–1996). b Area measurements: personal measurements. The number includes both full-shift and short-term measurements.…”
Section: Data Available For This Critiquementioning
confidence: 99%
See 1 more Smart Citation